Molecular analyses reveal a new species of Palmariaceae from Subantarctic Chile: Devaleraea yagan sp. nov. (Palmariales, Rhodophyta) - Bustamante, Danilo E.; Calderon, Martha S.; Mansilla Muñoz, Andres Omar (My University, 2022)
The red algal family Palmariaceae is distributed in the northern and southern hemispheres and currently includes four genera and 25 species. Recent studies based on transcriptome and organellar genome data strongly support a monophyletic family; however, this condition was not confirmed among its constituent genera. Additionally, no reliable morphological diagnostic features have been identified for delimiting Devaleraea and Palmaria. During expeditions to Subantarctic Chile along isolated channels and fjords to explore macroalgae diversity, we collected samples of specimens from the intertidal and assessed them using morphology and molecular markers (cox1, rbcL, nuclear-encoded ITS rDNA). Here we describe the new species Devaleraea yagan based on multilocus phylogeny and confirm the low genetic divergences in palmariaceaean species using principal coordinate analysis (PCoA). This new species is diagnosed by having its diminutive thalli attached to the substratum by a reduced holdfast and by the presence of rhizoidal cells in the medulla. Further analyses including genomic data of members of Devaleraea, Halosaccion and Neohalosacciocolax lineages are expected to support the taxonomic restructuring of the family.
Keywords: beagle channel; cox1; its rdna; magallanes; molecular phylogeny; pcoa; rbcl